Mural Paintings of Lampang School: The Analytical of Iconography and Factors that Influence Thosachat (The Last Ten Jatakas) Depicted on the Mural Paintings in Lampang Province Between the 18-19th Century A.D. - Meepukdee, Khomsi (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2020)
This research has two objectives which are to study the iconography of the characters in Thosachat, the last ten Jakatas, depicted on mural paintings in Lampang Province, and to analyze factors that could affect the adaptation of the Thosachat mural painting patterns by local artists called Sala in Lampang Province. According to the research, although the artists have diverse origins, from Lampang, Lampoon, Chiangmai, and Chiangrai, they share similar characteristics in mural painting. Murals will be painted according to Thai art and culture. They often painted important circumstances and incidents happening in Thosachat. The mural painting can be divided into two groups which are the mural painted before 1957 and the mural painted after 1957. By grouping the murals according to the periods, it clearly showed that the ones painted before 1957 were influenced by Ratanakosin, or Bangkok, art style. It can be noticed in the way how the paintings tell stories, usually important ones. Also, space usage, iconography, and costume of the characters represent Ratanakosin art which is very different from the style of mural painted after 1957 in which the artists express their own styles. It could be presumed that there are two main factors of the changes in mural painting tradition. First is the government factor which affected the mural paintings before 1957. There is evidence at Wat Bunya Wat, Wat Koh, and Wat Chang Puek showing the influence of Thai mural art during the King Rama 6 period. The other factor is the economic factor which clearly affected the mural paintings after 1957. Due to the widespread of caricature by S. Tham Pakdi. It is assumed that when there were co-hosts for merit-making, the mural painting paid by space occurred. This directly affected the direction of the paintings as it can be reproduced in different places.